2010
DOI: 10.1308/003588410x12628812460092
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of absent nerve conduction in older patients with bilateral carpal tunnel syndrome

Abstract: Ann R Coll Surg Engl 2010; 92: 403-405 403Carpal tunnel syndrome is common in the general population with approximately 1% incidence but can often be treated with simple night wrist splints.1 For those patients who do respond satisfactorily to conservative measures, surgical decompression is often successful.2 However, some investigators have reported that older patients can have a less satisfactory outcome after surgery, 3 though this impression is not universally shared. 4,5 To the author's knowledge, no obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…As has been reported previously (17,18,26) and confirmed in the present study, the severity of CTS increases with age. It is unclear why CTS in elderly patients is more severe.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As has been reported previously (17,18,26) and confirmed in the present study, the severity of CTS increases with age. It is unclear why CTS in elderly patients is more severe.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the present study was aimed to investigate whether measurement of the median nerve CSA actually contributes to assessing the severity of CTS. Because the risk of more severe CTS increases with age (17,18) and older patients have a less satisfactory outcome after surgery (19,20), the present study also was aimed to investigate the influence of aging on the median nerve CSA.…”
Section: Introductionmentioning
confidence: 99%
“…In a series involving patients aged >70 years, 80% of the patients demonstrated electrophysiological study results indicating severe dysfunction of the median nerve 25) . Other studies have also reported similar results in elderly patients with CTS 9,20) . It is suggested that results of NCS indicating severe disease could be related to delayed treatment owing to age-related reduced pain sensitivity because of reduced nerve membrane excitability 21) .…”
Section: Discussionsupporting
confidence: 72%
“…There are divided opinions regarding the impact of age on the efficacy of surgical decompression [2,3], but increasing evidence is mounting that older patients may have a less satisfactory outcome, though may still benefit from a release [4,5]. At the time of initial publishing, the article by Povlsen 'High incidence of absent nerve conduction in older patients with bilateral carpal tunnel syndrome' [6] was, to our knowledge, the first to suggest an explanation based on human patient data.…”
Section: Introductionmentioning
confidence: 99%
“…Since initial publication, further evidence has emerged that supports both the age-dependency of pre-operative conduction velocities in carpal tunnel syndrome, but also the rate of recovery of motor conduction post-operatively [6]. Explanations for these findings include 1) reduced pain sensitivity with age, thus delaying presentation in elderly patients with carpal tunnel syndrome to a point by which more severe and potentially irreversible nerve damage has already occurred [7] 2) the fact that aging even in healthy individuals reduces peripheral nerve conduction velocities [8] and 3) that aging reduces axonal regeneration capacity and Schwann cell neurotrophic factor production in animal models [9].…”
Section: Introductionmentioning
confidence: 99%